Demographic and clinical characteristics of participants in the Neuropsychiatric Genetics of African Populations-Psychosis (NeuroGAP-Psychosis) study: A descriptive analysis - Rocky E. Stroud; Kimberly Hook; Melkam Alemayehu; Lukoye Atwoli; Mark Baker; Lori B. Chibnik; Bizu Gelaye; Stella Gichuru; Symon M. Kariuki; Karestan C. Koenen; Joseph Kyebuzibwa; Justin McMahon; et al. (PLOS One, 2026)
Background Approximately 1.3 million individuals in sub-Saharan Africa, as well as millions of others worldwide, live with psychotic disorders. However, there is limited mental health research based on these populations and even less of a focus on neuropsychiatric genetics research within these settings. Methods To address this gap, the Neuropsychiatric Genetics of African Populations-Psychosis (NeuroGAP-Psychosis), a case-control study, collected data identifying genetic and environmental risk factors associated with psychotic disorders in Ethiopia, Kenya, South Africa, and Uganda. This paper describes baseline demographic and clinical characteristics of the 42,953 participants recruited between 2018–2023 and compares these characteristics by country and case status. Results Overall, 57.3% of participants were male (ranging from 65.8% in Ethiopia to 46.6% in Uganda). Among cases, the clinical diagnosis of schizophrenia or psychotic disorder not otherwise specified (NOS) ranged from 75.5% in Ethiopia to 44.4% in Uganda. Specific to bipolar disorder or mania NOS, the highest proportion was 53.9% in Uganda, and the lowest was 24.0% in Ethiopia. There were country-level and case-status differences across all demographic and clinical (e.g., physical comorbidities, substance use) variables. Conclusion Many factors, including language of consent, recruitment catchment areas, diagnostic practices across countries, and translation and/or cultural interpretation of the measures used in this study may account for the differences observed across countries. These findings suggest the importance of ongoing evaluation of cross-national differences to explore clinical implications and patterns of symptoms amongst geographically and culturally diverse populations. Future analyses should evaluate within-country differences to better explore these variations.